Heuristic algorithms for optimization of task allocation and result distribution in peer-to-peer computing systems - Chmaj, Grzegorz; Walkowiak, Krzysztof; Tarnawski, Michał; Kucharzak, Michał (Zielona Góra: Uniwersytet Zielonogórski)
Recently, distributed computing system have been gaining much attention due to a growing demand for various kinds of effective computations in both industry and academia. In this paper, we focus on Peer-to-Peer (P2P) computing systems, also called public-resource computing systems or global computing systems. P2P computing systems, contrary to grids, use personal computers and other relatively simple electronic equipment (e.g., the PlayStation console) to process sophisticated computational projects.
Keywords: P2P computing system; distributed computing; optimization; heuristics; evolutionary algorithms